Metode Bercerita untuk Ibu Karir dalam Memberikan Pendidikan Islam untuk Anak - Izzati, Kamila (Universitas Islam Madura, 2020)
Islamic education needs to be instilled in children from an early age, in this case the role of the family and the environment around the child is very important especially the role of a mother as the child's first madrasa. But in this era, many mothers were also found to be career women with a number of reasons behind this. The purpose of this study was to determine the effect of career women in providing Islamic education for their children and the effectiveness of the method of storytelling for career women in educating children. The sample of this study were 100 students of Electronic Engineering Polytechnic Institute of Surabaya, the majority of whom had mothers as a career woman. This study uses a qualitative analysis method seen from the statements presented by the sources and the results obtained that the method of storytelling is quite effective for career women in providing education to children.